FMR1 allele size distribution in 35, 000 males and females: a comparison of developmental delay and general population cohorts. (December 2018) - Kraan, Claudine; Bui, Quang; Field, Mike; Archibald, Alison; Metcalfe, Sylvia; Christie, Louise; Bennetts, Bruce; Oertel, Ralph; Smith, Melanie; du Sart, Desiree; Bruno, Damien; Wotton, Tiffany; et al.
Abstract Purpose Developmental delay phenotypes have been associated withFMR1 premutation (PM: 55–200 CGG repeats) and "gray zone" (GZ: 45–54 CGG repeats) alleles. However, these associations have not been confirmed by larger studies to be useful in pediatric diagnostic or screening settings. Methods This study determined the prevalence of PM and GZ alleles in two independent cohorts of 19, 076 pediatric referrals to developmental delay diagnostic testing through Victorian Clinical Genetics Service (cohort 1:N = 10, 235; cohort 2:N = 8841), compared with two independent general population cohorts (newborn screeningN = 1997; carrier screening by the Victorian Clinical Genetics Service prepair programN = 14, 249). Results PM and GZ prevalence rates were not significantly increased (p > 0.05) in either developmental delay cohort (male PM: 0.12–0.22%; female PM: 0.26–0.33%; male GZ: 0.68–0.69%; female GZ: 1.59–2.13-%) compared with general population cohorts (male PM: 0.20%; female PM: 0.27–0.82%; male GZ: 0.79%; female GZ: 1.43–2.51%). Furthermore, CGG size distributions were comparable across datasets, with each having a modal value of 29 or 30 and 1/3 females and 1/5 males having at least one allele with ≤26 CGG repeats. Conclusion These data do not support the causative link between PM and GZ expansions and developmental-delay phenotypes in pediatric settings.